From special to inclusive education policies in Austria – developments and implications for schools and teacher education. Issue 1 (1st January 2020) - Buchner, Tobias; Proyer, Michelle
ABSTRACT: This paper is concerned with the developments of inclusive education policies and their impact on teacher education in Austria today. As we argue, most policies concerning inclusive education are still reduced to a focus on disability. Such an approach can be explained, but not legitimised, by the historical development of the education of students with disabilities, which engendered specific tendencies in the evolution of policies of inclusive education and teacher education for inclusion. This policy evolution can be divided into three phases, which we analyse in detail in this paper: (1) the building of the special school system (the 1960s to mid 1980s), (2) establishing 'integrative education' structures and practices (mid 1980s – mid 2000s), and (3) efforts to make the Austrian education system more inclusive (2007 until today). The recent phase included a reform of teacher education for inclusive education, which, on the one hand, supports specific aspects of inclusive education, but, on the other hand, is still influenced by individual model discourses, rooted in the 1960s, such as binary groupings of students (dis/abled).